Monitoring System with Two Central Facilities Protocol - Caesar Firdaus; Wahyudin Wahyudin; Eddy Prasetyo Nugroho (Universitas Pendidikan Indonesia, 2017)
The security of data and information on government’s information system required proper way of defending against threat. Security aspect can be achieved by using cryptography algorithm, applying information hiding concept, and implementing security protocol. In this research, two central facilities protocol was implemented on Research and Development Center of Mineral and Coal Technology’s Cooperation Contract Monitoring System by utilizing AES and whitespace manipulation algorithm. Adjustment on the protocol by creating several rule of validation ID’s generation and checking processes could fulfill two of four cryptography objectives, consist of authentication and non-repudiation. The solid collaboration between central legitimization agency (CLA), central tabulating facility (CTF), and client is the main idea in two central facilities protocol. The utilization of AES algorithm could defend the data on transmission from man in the middle attack scenario. On the other hand, whitespace manipulation algorithm provided data integrity aspect of the document that is uploaded to the system itself. Both of the algorithm fulfill confidentiality, data integrity, and authentication.